2016
DOI: 10.3390/su8070683
|View full text |Cite
|
Sign up to set email alerts
|

Study on Industrial Integration Development of the Energy Chemical Industry in Urumqi-Changji-Shihezi Urban Agglomeration, Xinjiang, NW China

Abstract: Abstract:With industrial integration accelerating in domestic and foreign enterprise, industrial integration is becoming the only way for regional development to break through its bottleneck. Compared with advanced foreign enterprises, there exists a significant gap in regional industrial integration, especially in the urban agglomeration of the energy chemical industries of Urumqi-Changji-Shihezi in Xinjiang. Findings from field visits and quantitative analysis show that the energy chemical industry in urban … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…The central part of the study area is the urban center with the highest traffic volume. In addition, there are several mechanical and electrical industrial parks in the northeastern part of the study area [ 109 ]. Hou et al [ 110 ] reported on surface dust heavy metals in China for the last 10 years and found that traffic emissions were the largest source of heavy metals in 79% of the surveyed cities.…”
Section: Resultsmentioning
confidence: 99%
“…The central part of the study area is the urban center with the highest traffic volume. In addition, there are several mechanical and electrical industrial parks in the northeastern part of the study area [ 109 ]. Hou et al [ 110 ] reported on surface dust heavy metals in China for the last 10 years and found that traffic emissions were the largest source of heavy metals in 79% of the surveyed cities.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Urumqi has the largest transit hub in Xinjiang, which provides very essential conditions for industrial development between cities around Urumqi. Urumqi also tends to develop industrial cooperation with the surrounding cities, which have also driven the ID and promoted the efficient use of LRCC in other surrounding cities [56]. On the other hand, there is no leading city in southern Xinjiang where the natural environment is very harsh and the economic condition is very weak [57].…”
Section: Radiation Analysismentioning
confidence: 99%
“…Ref. [25] verified that isoliquiritigenin's antitumor action requires the presence of hydroxyl groups as functional groups. According to research [19], the best locations for chalcone compounds to substitute active groups are at positions 2′and 4′ of the A ring and 4 of the B ring.…”
Section: Introductionmentioning
confidence: 96%